Kontribusi Panjang Lengan dan Koordinasi Mata Tangan Dengan Ketepatan Pukulan Smash Pada Permainan Bulu Tangkis Siswa Madrasah Aliyah Usma Lambai Kabupaten Kolaka Utara - Igal Sanjaya, Resky Ana Abadi, Ika Sartika (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
This study aims to determine the Contribution of Arm Length and Hand Eye Coordination to the Accuracy of Smash Punches of Madrasah Aliyah Usma Lambai students in North Kolaka Regency. This research method used is quantitative, involving 30 students who became the research sample. Based on the results of the analysis, the significance value (sig) 0.000 is smaller than the probability value of 0.05 which indicates that arm length and hand eye coordination are significantly related to the accuracy of Badminton smash shots. The results of the analysis of the contribution of arm length and hand eye coordination to the accuracy of Badminton smash shots obtained a value of 68.1% or in the high correlation category.